2014
DOI: 10.1073/pnas.1316447111
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin expression by CD103dendritic cells drives intestinal inflammation

Abstract: Intestinal CD103 − dendritic cells (DCs) are pathogenic for colitis. Unveiling molecular mechanisms that render these cells proinflammatory is important for the design of specific immunotherapies. In this report, we demonstrated that mesenteric lymph node CD103 − DCs express, among other proinflammatory cytokines, high levels of osteopontin (Opn) during experimental colitis. Opn expression by CD103 − DCs was crucial for their immune profile and pathogenicity, including induction of T helper (Th) 1 and Th17 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 96 publications
1
59
1
Order By: Relevance
“…RNA extraction, quantification, and cDNA synthesis from isolated DCs or CD4 + T cells were performed as previously described (20). Primers were designed using the Primer 3 program and are as follows: Tigit sense primer, 59-GTGGGATTTACAAGGGGAGA-39 and antisense, 59-CTTCCAGGG-GATGAGAGAC-39; Gata3 sense primer, 59-TTACCACCTATCCGCCC-TAT-39 and antisense, 59-ACACACTCCCTGCCTTCTG-39; Cd226 sense primer, 59-CAAGAACACTGGCACAAAGA-39 and antisense, 59-GAAA-CAAGCAGGAGTAGATGC-39; c-maf sense primer, 59-CCCTTGA-CAGTTTGCTTCTA-39 and antisense, 59-CCCATTCTGCTATCTTTGAC-39; Rorc sense primer, 59-TGTTTTATGGGGTTTGGGTA-39 and antisense, 59-AAGAGATTGTGTGCCAGAG-39; and Tbx21 sense primer, 59-TAGTGATTGGTTGGAGAGGA-39 and antisense, 59-GTAGTTCGGGCA-GAGAAAG-39 (Eurofins MWG).…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction, quantification, and cDNA synthesis from isolated DCs or CD4 + T cells were performed as previously described (20). Primers were designed using the Primer 3 program and are as follows: Tigit sense primer, 59-GTGGGATTTACAAGGGGAGA-39 and antisense, 59-CTTCCAGGG-GATGAGAGAC-39; Gata3 sense primer, 59-TTACCACCTATCCGCCC-TAT-39 and antisense, 59-ACACACTCCCTGCCTTCTG-39; Cd226 sense primer, 59-CAAGAACACTGGCACAAAGA-39 and antisense, 59-GAAA-CAAGCAGGAGTAGATGC-39; c-maf sense primer, 59-CCCTTGA-CAGTTTGCTTCTA-39 and antisense, 59-CCCATTCTGCTATCTTTGAC-39; Rorc sense primer, 59-TGTTTTATGGGGTTTGGGTA-39 and antisense, 59-AAGAGATTGTGTGCCAGAG-39; and Tbx21 sense primer, 59-TAGTGATTGGTTGGAGAGGA-39 and antisense, 59-GTAGTTCGGGCA-GAGAAAG-39 (Eurofins MWG).…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…Primers for Cd155 were previously described (15). Real-time PCR was performed as previously described (20).…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…RNA extraction, quantification, and cDNA synthesis were performed as previously described (17). The sequences of RT-PCR primers used for mRNA relative expression analysis in this study were designed using the Tgfb1 FW: 59-CCTGGGTTGGAAGTGGA-39, Tgfb1 Rev: 59-TAGTA-GACGATGGGCAGT-39.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…The sequences of RT-PCR primers used for mRNA relative expression analysis in this study were designed using the Tgfb1 FW: 59-CCTGGGTTGGAAGTGGA-39, Tgfb1 Rev: 59-TAGTA-GACGATGGGCAGT-39. Real-time PCR was performed as previously described (17).…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…In addition, it has been observed that Th17 cytokine IL-17 levels enhance in CD [9]. OPN has been found to be over-expressed in plasma and intestinal tissue from patients with inflammatory bowel diseases and CD [12,13]. OPN expression by intestinal CD103-dendritic cells (DCs) has been demonstrated to drive intestinal inflammation [12,13].…”
mentioning
confidence: 99%